Morphological Parameters in Quadriceps Muscle Were Associated with Clinical Features and Muscle Strength of Women with Rheumatoid Arthritis: A Cross-Sectional Study - Leonardo Peterson dos Santos (MDPI AG, 2021)
Background: Rheumatoid arthritis (RA) is an autoimmune, inflammatory and chronic disease that may lead to loss of muscle mass, muscle strength and decreased functionality. Our objectives are to assess the quadriceps muscle morphology by ultrasound (MU) and verify its associations with clinical features, muscle strength and physical function in RA patients. Methods: In this cross-sectional study, RA women (≥18 years) were included. Morphological parameters in quadriceps muscle consisted of the muscle thickness and pennation angle of rectus femoris (RF), vastus intermedius (VI) and vastus lateralis (VL). RA activity was measured by a 28-joint disease activity score (DAS28), muscle strength by handgrip and chair stand tests, and physical function by health assessment questionnaire (HAQ), timed-up-and-go (TUG) test and short physical performance battery (SPPB). Results: Fifty-five patients were included (age: 56.73 ± 9.46 years; DAS28: 3.08 ± 1.29). Muscle thickness in RF, VI and VL were negatively associated with age (RF, p < 0.001; VI, p = 0.013; VL, p = 0.002) and disease duration (RF, p < 0.001; VI, p = 0.005; VL, p = 0.001), and were positively associated with handgrip strength (RF, p = 0.015; VI, p = 0.022; VL, p = 0.013). In addition, decreased muscle thickness in VI (p = 0.035) and a smaller pennation angle in RF (p = 0.030) were associated with higher DAS-28 scores. Conclusion: Quadriceps muscle morphology by ultrasound appears to be affected by age, disease duration, disease activity and muscle strength in patients with RA. MU can be a useful method to evaluate the impact of the disease on skeletal muscle.